Ornstein-Zernike correlations and magnetic ordering in nanostructures (2014)
ABSTRACT: In this paper we propose a Heisenberg variational approach to study pseudo-critical phenomena on ferromagnetic nanostructures. We combine a two-spin cluster 3-dimensional Heisenberg hamiltonian with Orstein-Zernike correlations and consider several geometries and crystalline lattices to explore the relationship among these factors and the effective number of nearest neighbors defined in several kind of nanometric structures. With this method we examine the size at which the pseudo-critical temperature of a magnetic nanoparticle reaches its bulk value. Our results shed light on the nanoscopic-microscopic limit, evidencing in particular that when one dimension is very small, independently of how big the other dimensions become, it is not possible for the structure to reach the bulk-like behavior. The results of our model are in good agreement with experimental data and other available analytical models.